Long-Term Follow-Up Results of Mechanical Wrist Traction as Non-Invasive Treatment for Carpal Tunnel Syndrome - Meems, Margreet; Boekhorst, Myrthe G. B. M.; Pop, Victor J. M. (Frontiers in Neurology, 2021)
Background: For patients with carpal tunnel syndrome (CTS), carpal tunnel release surgery is the only known treatment option with long-term positive effects. Up to one-third report recurrent symptoms and 12% needs repeated surgery. This study aimed to evaluate the long-term effects of mechanical traction as a non-invasive treatment option for CTS compared to care as usual. Methods: Patients with electrodiagnostically confirmed CTS (N = 181, mean age 58.1 (13.0) years, 67% women) were recruited from outpatient neurology clinic in the Netherlands. Patients completed baseline questionnaires, and randomized to the intervention group (12 treatments with mechanical traction, twice a week for six weeks) or care as usual. The primary clinical outcome measure was surgery during 12 months follow-up. Secondly, we assessed symptom-severity with the Boston Carpal Tunnel Questionnaire (BCTQ) at baseline, 3, 6 and 12 months follow-up. Changes in CTS symptom-severity between baseline and 12 months follow-up were analyzed between groups using t-tests and a multiple linear regression analyses, adjusting for duration of complaints, age, gender and symptom severity at baseline. Results: At 12 months follow-up, 35 of 94 (37%) patients in the intervention group had surgery, compared to 38 of 87 (44%) in the care as usual group (χ21 = 0.78, p = .377). Symptom-severity and functional status scores did not significantly differ between the intervention (n = 81) and care as usual group (n = 55) at follow-up. For the patients who did not have surgery, BCTQ scores decreased significantly more from baseline to 12 months follow-up in intervention group (n = 53) compared to patients in the care as usual group (n = 25). For patients who did not have surgery, belonging to the intervention group and a higher BCTQ score at baseline were related to a greater decrease in BCTQ scores from baseline to 12 months follow-up, as well as symptom-severity and functional status. Conclusions: Mechanical traction is effective in reducing symptom severity compared to current conservative treatment options in standard care and can therefore benefit the large number of patients that prefer conservative treatment for CTS. Trial registration: Clinical Trials NL44692.008.13. Registered 19 September 2013, https://clinicaltrials.gov/ct2/show/NCT01949493